Phosphorus application effects on seeding chia - Domingues, Lucas Zanin; Silva, Tiago Roque Benetoli; Brondani, Silene Tais (Acta Iguazu, 2020)
Chia (Salvia Hispanica L.) is an annual herbaceous plant belonging to the family Lamiaceae, with large proportions of omega-3, omega-6, antioxidants, fibers and proteins in its composition. Information and recommendations on its cultivation are still limited, as interest in the plant is recent. Thus, the objective of this work is to verify the effects of the application of phosphorus doses in the sowing of chia. The experiment was conducted under field conditions, at Fazenda da Universidade Estadual de Maringá, at the Umuarama Regional Campus. The soil of the place where the typical Dystrophic Red Latosol, with sandy texture experiment was implanted. The experimental design was a randomized block with five treatments and five replicates. The treatments were composed of five doses of phosphorus at sowing (0, 30, 60, 90, 120 kg ha-1). The dry mass of the aerial part, final population of plants, mass of 1,000 grains, productivity and oil content were evaluated. Phosphorus rates application at sowing provided positive increases in the vegetative and reproductive chia development.